Toxic effects of the neem oil (Azadirachta indica) formulation on the stink bug predator, Podisus nigrispinus (Heteroptera: Pentatomidae) - Zanuncio, Jose Cola; Mourao, Sheila Abreu; Martinez, Luis Carlos; Wilcken, Carlos Frederico [UNESP]; Ramalho, Francisco S.; Plata-Rueda, Angelica; Soares, Marcus Alvarenga; Serrao, Jose Eduardo (Nature Publishing Group, 2016)
This research investigated the effects of neem oil on mortality, survival and malformations of the nontarget stink bug predator, Podisus nigrispinus. Neurotoxic and growth inhibitor insecticides were used to compare the lethal and sublethal effects from neem oil on this predator. Six concentrations of neem oil were topically applied onto nymphs and adults of this predator. The mortality rates of third, fourth, and fifth instar nymphs increased with increasing neem oil concentrations, suggesting low toxicity to P. nigrispinus nymphs. Mortality of adults was low, but with sublethal effects of neem products on this predator. The developmental rate of P. nigrispinus decreased with increasing neem oil concentrations. Longevity of fourth instar nymphs varied from 3.74 to 3.05 d, fifth instar from 5.94 to 4.07 d and adult from 16.5 and 15.7 d with 0.5 and 50% neem doses. Podisus nigrispinus presented malformations and increase with neem oil concentrations. The main malformations occur in wings, scutellum and legs of this predator. The neem oil at high and sub lethal doses cause mortality, inhibits growth and survival and results in anomalies on wings and legs of the non-traget predator P. nigrispinus indicating that its use associated with biological control should be carefully evaluated.